Analisis Dan Rancangan Penyusunan Laporan Keuangan Berdasarkan SAK EMKM (Studi Kasus Pada UMKM Sale Pisang Bawana Sari) - Amelia, Nova; Mulyandani, Vina Citra (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
Financial reports are important for every business because financial reports contain information that shows the company's financial condition. The research was conducted at Sale Pisang Bawana Sari UMKM to find out how the financial recording system and the preparation of financial reports had been carried out by the company. The method used is descriptive qualitative with data collection techniques in the form of interviews, observations and documentation. The results of the study showed that Sale Pisang Bawana Sari UMKM had not kept financial records properly and had not prepared financial reports due to a lack of understanding regarding the preparation of financial reports. Therefore, in this study a draft accounting bookkeeping and preparation of Financial Reports based on SAK EMKM were prepared which consisted of Profit and Loss Reports, Balance Sheet, and CALK for the period October 2022-December 2022.